Effect of Perceived Price, Muslim Service Quality and Halal Certification on Purchase Decision Gacoan Noodles Through Application : Shopee Users Shopeefood Feature - Anggriani, Heni; Aang Gunaepi; Ahmad Nuh (Jurnal Ecoment Global, 2024)
Abstract  Objective: This research aims to find out how much influence Perceived Price, Muslim Service Quality and Halal Certification have on Gacoan Noodles Product Purchasing Decisions through the Shopee Food App Customer Case Study Application. Design/Methods/Approach: The sampling in this study used purposive samplings with respondents of 302 people who were resident in various regions of Indonesia and had purchased Gacoan Noodles through a shopee app. In this study, perceived price, Muslim service quality and halal certification as free variables or independent variables while purchasing decisions as bound or dependent variables. The type of research used in this research is a quantitative method. Data analysis using SPSS software 23. Data analysis techniques in this study use data quality testing methods, classical assumption testing and regression testing. Findings: The results of this study show that partially variable perceived price and Muslim service quality have a positive and significant influence on purchasing decisions. As for the halal variable, certification has no positive and significant influence on the purchase decision. Originality/Value: This study  builds  upon  previous  research  that  discusses  the effect of variables that can make customer decision to buy, by adding buy with application delivery food. Practical/Policy implication: This research is expected to provide input for company to maximize factor-factor costumer decision buying product by right strategy. Keywords: Perceived Price, Service Quality, Halal Certification, Purchase Decision